A NEO-ASSYRIAN PROVINCIAL PALACE AT TELL BILLA. (December 2021) - Creamer, Petra M.
Abstract : The Neo-Assyrian site Šibaniba (modern Tell Billa) served as a provincial center at the very edge of what is traditionally known as the "Assyrian Heartland". Excavations in the early 1900s under Dr. Speiser of the University of Pennsylvania uncovered architecture in the southwestern portion of the mound, but a loss of records and lack of publication have prevented any comprehensive publications or analysis of the archaeological material. The architecture from Level I in the southwest corner is the remains of a palace from the latter half of the Neo-Assyrian period – comprised of an inner, paved courtyard and surrounding rooms. The analysis of this palace complex is carried out herein, with a discussion of its positioning and importance, especially during Nineveh's tenure as imperial capital. Overall, Šibaniba, despite being located so close to the Heartland, was an important administrative center in its own right – illustrated by a restructuring of the citadel's organization in the later Neo-Assyrian period and its inclusion in Sennacherib's irrigation program.